Existência e unicidade de solução para a equação da onda no sentido clássico - PIRES JUNIOR, Gilberto Gil Asevedo (2023)
In this paper we investigate the mathematical model for the wave equation in the classical sense of Newton and Leibniz. Our goal is to present the existence and uniqueness of the solution as well as the continuous dependence on the initial data. We present these solutions according to D'Alembert's method.